PELAKSANAAN RAPAT PERMUSYAWARATAN DALAM PERADILAN TATA USAHA NEGARA - Ristandi Pradana, I Putu; -, Marwanto (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
Consultative Meeting (the dismissal process) is a preliminary stage before the examination principal dispute in the Administrative Court. Consultative Meeting is examining the lawsuit that authorizes the chairman of the Court not to accept or declare the lawsuit is unfounded with a stipulation. This provision is found in Article 62 of Act. No 5 of 1986. Within 14 days of the determination of the reading, do the resistance will be checked proceeding.
Keywords: Consultative Meeting, the Administrative Court, the lawsuit